Modelagem de processos de negócios na implementação de ERPs nacionais em PMEs Business processes modeling in the implementation of national ERPs within SMEs - Fernanda Pereira Carneiro da Silva; Néocles Alves Pereira (Production)
Este artigo apresenta evidências encontradas em uma pesquisa que teve como objetivo investigar a contribuição do uso da Modelagem dos Processos dos Negócios (MPN) na implementação do Enterprise Resource Planning (ERP) em pequenas e médias empresas (PMEs). Foi observado, nos principais fornecedores nacionais deste sistema, o uso da MPN, verificando sua influência na integração dos processos internos dos negócios de seus clientes. Para esta investigação buscaram-se as informações nos fornecedores nacionais de sistema ERP e seus clientes, mediante questionários específicos. Esta pesquisa possibilitou obter informações reais das principais características de implementação nas PMEs, destacando-se como a MPN contribui efetivamente na implementação para otimizar a integração dos processos internos dos negócios. This article presents evidences found in a research whose objective was to investigate the contribution of using business processes modeling (BPM) in the implementation of Enterprise Resource Planning (ERP) in small and middle companies (SMEs). The use of the BPM and assessment of its influence for the integration of the internal business processes of their customers, was also observed in the main national ERP system suppliers. To carry out this research, information was obtained by means of specific questionnaires answered by the national ERP system suppliers and their customers. This research allowed to obtain actual data about the main implementation characteristics within the SMEs, showing how the BPM effectively contributes for the implementation and better integration of the internal business processes.